Preparation and Characterization of Ag Incorperarted MnWO4/Zeolite Composites by Microwave-Assisted Metathetic Reaction - Sung Lim, Chang (Asian Journal of Chemistry, 2012)
Ag-MnWO4/zeolite-A porous composites were synthesized using a solid-state metathetic method with microwave irradiation. The characteristics of the solid-state metathetic reaction and the formation of by-product NaCl were found to drive the reaction for wolframite-type MnWO4 toward completion. The Ag-MnWO4/zeolite-A porous composites were formed completely at 600 ºC. Monoclinic-like crystals of MnWO4 were primarily co-mixed with porous zeolite-A. Small spherical silver particles were immobilized in the porous MnWO4/zeolite-A matrix.